2020
DOI: 10.3390/pharmaceutics12090787
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Membrane Components from Neisseria gonorrhoeae Using Catanionic Surfactant Vesicles: A New Approach for the Study of Bacterial Surface Molecules

Abstract: Identification of antigens is important for vaccine production. We tested extraction protocols using cetyltrimethylammonium tosylate (CTAT) and sodium dodecylbenzenesulfonate (SDBS) to formulate surfactant vesicles (SVs) containing components from Neisseria gonorrhoeae. Carbohydrate and protein assays demonstrated that protein and carbohydrates were incorporated into the vesicle leaflet. Depending on the extraction protocol utilized, 100–400 µg of protein/mL of SVs solution was obtained. Gel electrophoresis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We are interested in anionic SDBS/CTAT SVs due to their potential as drug delivery vehicles, vaccine platforms, 6 and systems used to investigate carbohydrate-protein interactions 7–9 and bacterial surface molecules. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in anionic SDBS/CTAT SVs due to their potential as drug delivery vehicles, vaccine platforms, 6 and systems used to investigate carbohydrate-protein interactions 7–9 and bacterial surface molecules. 10…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in anionic SDBS/CTAT SVs due to their potential as drug delivery vehicles, vaccine platforms, 6 and systems used to investigate carbohydrate-protein interactions [7][8][9] and bacterial surface molecules. 10 Anionic SVs are attractive for drug delivery and vaccine applications due to their ease of preparation and functionalization, and payload capacity. It has been demonstrated that small molecules can be incorporated into vesicles, 3,11,12 and vesicles have been functionalized with carbohydrates, 6,8 biotin, 13 folic acid, and peptides.…”
Section: Introductionmentioning
confidence: 99%